D5. Is maternal arterial function impaired in pregnancies with fetal growth restriction?. (12th August 2016) - Tay, J.; Foo, L.; McEniery, C.; Wilkinson, I.; Lees, C.
Abstract: Introduction : Studies in pre-eclampsia have demonstrated that central haemodynamic changes give more insight than peripheral measures into maternal cardiac and vascular physiology. This study aims to investigate augmentation index (AIX) and pulse wave velocity (PWV) in pregnancies affected by fetal growth restriction (FGR) and compare them to healthy women in the third trimester of pregnancy. Augmentation index (AIx) is a measure of systemic arterial stiffness derived from the ascending aortic pressure waveform. PWV is widely used as measure of arterial stiffness and predictor of future cardiovascular risk outside pregnancy. Methods : Eight pregnancies with fetal growth restriction (AC < 10th percentile and raised umbilical PI) in the third trimester (27–35 weeks gestation) were compared with 42 healthy pregnancies in similar gestation band. AIX and PWV were measured by the Vicorder device with women in the left lateral position. Unpaired t -test was used to calculate the p values amongst these groups. Results : The mean AIX in pregnancies with FGR was 22.63 compared to 10.10 in healthy pregnancies ( p  = 0.0005). PWV was 8.15 in the FGR group compared to 7.08 in healthy controls ( p  = 0.004). See charts. Conclusions : These results show that pregnancies affected by third trimester FGR in the absence of pre-eclampsia show impairment of maternal arterial function with high arterial stiffness. To date, many studies have shown impaired maternal arterial function in preeclampsia but little has been done to characterize maternal arterial function in fetal growth restriction alone. Considering both these conditions are thought to have common underlying etiology, these results suggest that arterial function is impaired in fetal growth restriction independent of hypertension or pre-eclampsia. Characterization of arterial profile could play an important role in the understanding of the etiology of this condition which has hitherto been ascribed purely to placental dysfunction.